Analisis Kesalahan Morfologis pada Karangan Narasi Ekspositoriik Siswa MTs N 2 Palu - Marfuah, Julia; Bakri, Taqyudin; Syam, Agustan (Jurnal Kreatif Online, 2020)
In using language, both spoken and written, an underlying theory is needed. The scope of language errors includes errors in phonology, morphology, the field of syntax, and the field of EYD. However, the purpose of this study only focused on the field of morphology in describing misuse of use: prepositions, affixes, and dotted words in narrative essays of class IXA students at MTs Negeri Palu Barat. This research was a qualitative research which aims to understand the phenomenon of what the research subjects experience holistically and by means of descriptions in the form of words and language, in a special natural context and by utilizing various scientific methods. Data collection techniques used in this study were observation, interviews, and documentation of the implementation of activities. The subjects of this study were 29 students of class XI A MTs N 2 Palu. The results of the research on the analysis of morphological errors in the expository narrative essay of MTs Negeri 2 Palu students were: (1) the form of misuse of prepositions which are sequenced from the words that follow them, such as the word dipalu, the use of the prepositions should be separated from the words that follow as in the word di Palu; (2) the form of the misuse of the affixation which is separated from the word that follows it as in the word di pilih, the use of the affixation should be linked to the word that follows it like the word dipilih; and (3) the form of misuse of the word berklitik which is separated from the word that follows it, as in the word ku menangkan, the use of the word that follows it should rely on the word that follows it as in the word kumenangkan.